Review on Effect of Supplementation with Iron-Rich Products to combat Anemia among Adolescent Girls (International Journal of Food and Nutritional Sciences, 2022)
Nutritional deficiencies are linked to a variety of health issues. Insufficient healthy red blood cells or hemoglobin may lead to an illness known as anemia. Hemoglobin is the primary blood protein responsible for transporting O2 to body cells. Heavy blood loss, persistent chronic disorders, and inadequate nutrition are the primary contributors to anemia. Many teenage girls cannot get enough iron from their diets to meet their high physiological needs for developing body tissues, making more RBCs, and starting menstruation. Anemia due to nutritional inadequacy is mostly caused by a lack of iron, vitamin B12, and vitamin C. Supplementation is recommended as a treatment for anemia caused by iron deficiency. Even though iron from herbal sources is less readily absorbed than inorganic or organic derivatives of iron produced by chemical synthesis, dietary supplements containing iron from herbal sources are still widely used, especially among people who are attracted to the idea of "getting back to nature." The main aim of this review is to see the effect of supplementation (Gogu plants, Curry leaves, Pearl millets, Moringa Oleifera) with iron-rich products to combat anemia among adolescent girls.